Mīr Ahmad Kashshī : His Biography and Sufi path According to the Manuscript of his ‘Tuhfa al-Rasūl and Farīd al-Maktūbāt’ - yalda azarmi; Najaf Jowkar (تاریخ ادبیات)
AbstractTuhfa al-Rasūl and Farīd al-Maktūbāt [=The Gift of the Prophet and The Unique Writing] written by Mīr Aḥmad Kashshī, one of the major Naqshbandī Sufi masters of Transoxania in the 19th century ACE, is a book regarding the Sufism of Khājagān [=the Nobles] in which following the trilogic tradition of Sharīʻa [=Islamic Law], tarīqa [=Sufi Path] and haqīqa [the Truth] the author commences the first chapters through Islamic law and legal antecedents in order to train and cultivate Naqshbandī novices. Then he delves more deeply into Sufism ipso facto in the rest of the labor. The dogmatic elements of mystical theology are outstanding in the work, and one can regard the book as an exemplary portrait of Sufism in the time of decadence. In this article, utilizing the transmissive resources, specifically references to the text perse, we introduce the audience descriptively and analytically with the manuscript to indicate the significance and necessity of an inquiry in the traditional Sufism of Naqshbandīs in Transoxania.